Assessing toxicities of industrial effluents and 1,4-dioxane using sulphur-oxidising bacteria in a batch test - Gurung, A.; Kim, S.H.; Joo, J.H.; Jang, M.; Oh, S.E. (2012)
In this study, the qualities of the final effluents from nine different industries (A, B, C, D, E, F, G, H and I) discharging 1,4-dioxane mainly as effluents were assessed using sulphur-oxidising bacteria (SOB) as a test micro-organism in batch mode. Results showed that effluent from industry 'B' was the most toxic of all the effluents tested, followed by E, C and A effluents. An EC50 value of 13 was obtained for effluent from B, whereas with E, C and A effluents, the EC50 values of 23, 25 and 29 were found, respectively. Similarly, batch tests were performed in order to evaluate the potential for 1,4-dioxane to inhibit growth on SOB. The lowest test concentration of 1,4-dioxane (12Î¼g/L) resulted in 17 of inhibition of SOB, whereas the highest test concentration (3.125mg/L) resulted in >75 of the inhibition. An EC50 value of 0.105mg/L was obtained for 1,4-dioxane. Â© 2011 The Authors. Water and Environment Journal Â© 2011 CIWEM.